Fasting Total Cholesterol with HIIT: Acute Response 20 Minutes After a Single 20-Minute HIIT Ergocycle Session in Young Men - gosy endra Vigriawan; mahmud yunus``; moch. yunus; Fajar Syamsudin; Dio Alif Airlangga Daulay; Ibnu Yusron (Gladi : Jurnal Ilmu Keolahragaan, 2026)
This study aimed to determine whether total cholesterol levels differed between 10 minutes before exercise and 20 minutes after a single session of high-intensity interval training (HIIT) performed on an ergocycle under overnight fasting conditions. This quantitative study employed a one-group pretest–posttest design. The participants were 41 healthy male university students aged 20–21 years with a body mass index of 20–23.9 kg/m² who met the inclusion criteria. All participants underwent overnight fasting for at least 8 hours, with water intake permitted, and avoided strenuous physical activity for 48 hours before testing. Total cholesterol was measured using an EasyTouch point-of-care device from capillary blood samples collected before and after a 20-minute HIIT ergocycle session. Data were analyzed using the Shapiro–Wilk normality test and a paired-samples t-test, with statistical significance set at p < 0.05. The results showed that 97.6% of participants experienced a decrease in total cholesterol, with mean values declining from 183.93 ± 12.10 mg/dL before exercise to 168.78 ± 12.77 mg/dL after exercise. The difference was statistically significant, t(40) = −13.43, p < 0.001, with a large effect size (Cohen’s dz = −2.10). In conclusion, a single HIIT ergocycle session was associated with an acute reduction in measured total cholesterol concentration during early recovery under overnight fasting conditions.